PLANEJAMENTO PUBLICITÁRIO NO SETOR FARMACÊUTICO DA FRONTEIRA OESTE DO RIO GRANDE DO SUL - DELEVATI, CRISTIANO; PEREIRA, JOÃO A.; DALCIN, MARCO A.; GODOY, RODRIGO; MOLIN, TIAGO D. (Salão do Conhecimento, 2013)
Resumo